Faktor-Faktor yang Memengaruhi Instrumen Pengendalian Akuntansi Manajemen dan Dampaknya terhadap Perkembangan Batik di Kabupaten Pamekasan - Nurhayati Nurhayati; Nita Octarina (Jurnal Manajemen dan Organisasi, 2020)
This study aims to determine what factors influence the use of management accounting in Batik SMEs in Pamekasan Regency and how it influences the use of management accounting applications related to control instruments. This research method uses a quantitative approach. The population in this study is the owner of batik SMEs in Pamekasan Regency. The sample was determined using a purposive sampling method with a total of 44 respondents. Data collection was done byinterview techniques and questionnaire distribution. Analysis of the data used in this study is SEM-PLS using the SMARTPLS 3.0 application. The results showed that education and financing did not affect the use of management accounting related to control instruments, whereas accounting training and business scale influenced the use of management accounting related to control instruments. The effect of the use of management accounting on batik SMEs in Pamekasan Regency has a positive effect on business development. After applying management accounting, SME owners can carry out planning and supervision in the operations of SMEs, in other words management accounting strongly supports business success.